Engagement Factors and Influence on Employee Turnover Intention at PT. Bank Negara indonesia (Persero) Tbk Mataram Branch Office - Wendy Prima J Putera; Anik Hermaningsih (Dinasti Publisher, 2022)
Turnover Intention is the tendency of employees to stop or intention to move to work elsewhere. Having employees coming in and out will be a burden for the company in recruiting more professional staff, so this is a serious problem and the company must know the factors that cause employee turnover. The purpose of this study was to determine the effect of Reward, Supervisor Support, and Organizational Justice on Engagement and to determine the effect of Engagement on BNI Mataram Branch Employee Turnover Intentions. The population used in this study is permanent employees BNI Mataram Branches many as 181 employees with the Total Sampling technique. To test the hypothesis in this study, researchers used the covariance-based Structural Equation Modeling (SEM) data analysis method with the help of the Smart-PLS program application. The results of the study show that Reward has no significant effect on Employee Engagement, Supervisor Support has a significant effect on Employee Engagement, Organizational Justice has a significant effect on Employee Engagement, and Engagement has a significant effect on Employee Turnover Intentions at BNI Mataram Branch.